Surface property modification of vanilla pods (Vanilla planifolia) treated with an ultrasound probe to increase the efficiency of solid–liquid extraction - Vargas-García, Karen Aylin; Aguilar-García, Magbis Azgad; Ochoa-Martínez, Luz Araceli; Esquivel-González, Blanca Edith; Bustos-Ramirez, Karina; Avendaño-Vásquez, Gilda; Varela-Santos, Elizabeth del Carmen (Frontiers in Food Science and Technology, 2025)
Vanilla is a flavoring of great culinary value worldwide. The conventional extraction process takes a long time and has high production costs, due to the characteristics of the pod, which contains compounds such as waxes, gums, resins, and fixed oils. This research introduces an ecofriendly methodology to increase the efficiency of solid–liquid extraction on vanilla pods using a sustainable alternative. Ultrasound processing conditions were time (2 min, 4 min, 6 min, 8 min, and 10 min), amplitude (50%, 75%, and 100%), and solvent (0, 60%, and 100% EtOH), and a solid: liquid ratio of 1:10 (pod: solvent) was used. The effect of the pretreatment on extraction efficiency was evaluated as a function of the vanillin concentration (yield). The optimization of the process was carried out with the Minitab 17 software. Surface properties were evaluated in terms of contact angle, adhesion work, and surface energy using the drop method (DropSnake software and LB-ADSA) and the Young and Dupré equations. A surface contact regime was employed to show the induced microstructure and hydrophobic-hydrophilic character after ultrasound pretreatment. Results suggested that the optimal pretreatment was 10 min, 100% amplitude, and 60% ethanol, obtaining an extraction yield of vanillin of 2,703.45 ± 33.25 μg/mL with a significant difference with respect to the control using natural convection (1701.33 ± 23.85 μg/mL, p > 0.05, R2>99). Reductions in the contact angle, in addition to high work adhesion and surface tension values, demonstrated the hydrophilic characteristics of the vanilla pods, and confirmed the modification of surface properties and the opening of diffusion channels related to the increase of the solvent intrusion on the vanilla pod surface after the ecological physical treatment. The results from this work indicate that using ultrasound as a pretreatment in the solid–liquid extraction process might further improve the performance in the extraction of vanillin and reduce the extraction time.